(untitled) (Нововведения Cовременного Научного Развития в Эпоху Глобализации: Проблемы и Решения, 2024)
This article explores the critical role of translation in the globalization of literature, emphasizing how it facilitates cross-cultural communication, enhances global literary exchange, and contributes to the preservation and dissemination of diverse cultural identities. By bridging linguistic barriers, translation allows readers worldwide to access works from different cultures, thus fostering a global literary community.